2012
DOI: 10.1186/1743-422x-9-190
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-6 and CCL5 (RANTES) in human respiratory epithelial (A549) cells by clinical isolates of respiratory syncytial virus is strain specific

Abstract: BackgroundRespiratory syncytial virus (RSV) is the major respiratory pathogen of infants and young children. During each seasonal epidemic, multiple strains of both subgroup A and B viruses circulate in the community. Like other RNA viruses, RSV genome replication is prone to errors that results in a heterogeneous population of viral strains some of which may possess differences in virulence. We sought to determine whether clinical isolates of RSV differ in their capacity to induce inflammatory cytokines IL-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…This may be similar to what has been proposed for RSV, suggesting that the induction of pro-inflammatory cytokines relates to genetic polymorphisms of the virus (Levitz1 et al 2012). The IBV/Brazil/PR05 strain is a S1 variant IBV, and regarding the results presented herein, it's nephropathogenic and the induction of IL-6 may be related to genetic variation of the S1 gene and its consequent induction of proinflammatory cytokines, agreeing with other studies using models of RNA virus (Hornsleth et al 1998, Montassier et al 2008, Levitz et al 2012, Montassier et al 2012.…”
Section: Discussionsupporting
confidence: 79%
“…This may be similar to what has been proposed for RSV, suggesting that the induction of pro-inflammatory cytokines relates to genetic polymorphisms of the virus (Levitz1 et al 2012). The IBV/Brazil/PR05 strain is a S1 variant IBV, and regarding the results presented herein, it's nephropathogenic and the induction of IL-6 may be related to genetic variation of the S1 gene and its consequent induction of proinflammatory cytokines, agreeing with other studies using models of RNA virus (Hornsleth et al 1998, Montassier et al 2008, Levitz et al 2012, Montassier et al 2012.…”
Section: Discussionsupporting
confidence: 79%
“…Although recent evidence suggests that circulating RSV strains exhibit slow rates of evolution [58], they may also differ in their capacity to induce pro-inflammatory cytokines [49]. Our analysis of the infected lung macrophage cells indicates a sustained pro-inflammatory cytokine response in the absence of productive infection.…”
Section: Discussionmentioning
confidence: 80%
“…Disease severity due to RSV infection is likely to be partly determined by a combination of the genetic characteristics of the host [48] and the capacity of different RSV strains to induce pro-inflammatory cytokines[49]. In addition RSV can cause a persistent infection in susceptible hosts correlating with prolonged disease symptoms [50].…”
Section: Discussionmentioning
confidence: 99%
“…The L protein was aligned using ClustalW. Accession numbers for all isolates used can be found within the materials and methods section of the paper to elevated CXCL8 levels in PIV infection in vitro, which may explain the elevated CXCL8 levels across all three viruses we observed here [15,41]. It has been shown that in A549 cells, specifically, HPIV-3 induced high levels of CXCL8 [42].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, IL-6 plays a pivotal role in bridging innate and acquired immune responses [11]. Since IL-1b, IL-6, and CXCL8 are secreted at high levels during respiratory viral infections, their induction likely contributes to the pathophysiology seen in patients [3,8,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%